2021
DOI: 10.1093/nar/gkab1131
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRroots: on- and off-target assessment of RNA-seq data in CRISPR–Cas9 edited cells

Abstract: The CRISPR-Cas9 genome editing tool is used to study genomic variants and gene knockouts, and can be combined with transcriptomic analyses to measure the effects of such alterations on gene expression. But how can one be sure that differential gene expression is due to a successful intended edit and not to an off-target event, without performing an often resource-demanding genome-wide sequencing of the edited cell or strain? To address this question we developed CRISPRroots: CRISPR–Cas9-mediated edits with acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…Additionally, the GC content of the sgRNA was also found to correlate with the off-target effect, enabling researchers to select more effective sgRNAs by their GC content [ 134 ]. Moreover, using Cas9 mRNA or protein instead of plasmids could also effectively reduce the off - target rate [ 151 , 152 ]. A mutant of Cas9, xCas9, is more precise than Cas9, can effectively reduce the off-target rate, and has been successfully used in gene therapy [ 153 ].…”
Section: Directions For Future Developments Of the Crispr/cas9 Systemmentioning
confidence: 99%
“…Additionally, the GC content of the sgRNA was also found to correlate with the off-target effect, enabling researchers to select more effective sgRNAs by their GC content [ 134 ]. Moreover, using Cas9 mRNA or protein instead of plasmids could also effectively reduce the off - target rate [ 151 , 152 ]. A mutant of Cas9, xCas9, is more precise than Cas9, can effectively reduce the off-target rate, and has been successfully used in gene therapy [ 153 ].…”
Section: Directions For Future Developments Of the Crispr/cas9 Systemmentioning
confidence: 99%
“…Differential expression analysis was carried out using DESeq2 v1.22.2 ( Love et al, 2014 ) and genes with Benjamini and Hochberg (1995) adjusted Wald test p -value < 0.05, absolute log2 fold change >1, and mean of normalized counts >10 were considered significant. The workflow includes RseQC v.4.0.0 ( Wang et al, 2012 ) for the confirmation of the library strandness and the verification of the editing status at on-target and potential off-target sites with CRISPRroots v.1.2 ( Corsi et al, 2022a ). Potential off-targets identified by CRISPRroots as high-risk were validate by sequencing, and no off-target edit was found ( Corsi et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of on/off-target sites in de novo transcriptome assembly was performed with Crisflash v.1.2.0( 43 ). Our off-target detection focused on up to 11nt mismatches and NRR PAM because the previous off-target reports indicated that off-target sites with ≥10 nt mismatches and NGG/NAG/NGA/NAA PAM exist 24,44 , although not with a high frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Gorodkin and Seemann have previously reported that off-target sites affect the expression profile of LOF samples using reference-based RNA-seq analysis. Our study used the GRIN2B dataset to benchmark de novo transcriptome assembly based and referencebased RNA-seq analyses( 44 ). Moreover, we profiled the on/off-target assessment of GRIN2B-REV sgRNA.…”
Section: Methodsmentioning
confidence: 99%